Tenure reform and perceived food security in Indonesia: An exploratory study - Liswanti, N.; Kirby, D.; Tamara, A.; Juniwaty, K.S.; Mwangi, E. (Center for International Forestry Research, 2021)
Land and forest tenure reform has been expanding globally, increasingly with the aim of improving the livelihoods and food security of indigenous people and local communities through securing forest access. In Indonesia, legal rights for local communities to access and manage state forests were partially recognised in 1999. Social forestry only started to advance in 2014, however, following the government’s pledge to transfer the management of 12.7 million ha of forest to forest-dependent communities. Evaluating the impact of these forest tenure reforms on local communities’ food security is critical to understanding the effectiveness of the reforms.